PEMERIKSAAN CKMB DAN HS-TROPONIN T PADA PASIEN INFARK JANTUNG DENGAN PENINGKATAN SEGMEN NON-ST - AK Salim; M Suryaatmadja; DA Hanafi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Acute Coronary Syndrome (ACS)1 is a typical chest pain symptom due to ischemic coronary insufficiency caused by blockage of acoronary artery thrombus. There are three different states: Unstable Angina (UA), Non-ST segment Elevation Myocardial Infarction(NSTEMI) and ST segment Elevation Myocardial Infarction (STEMI).1 Cardiac Troponin (cTn) is a myocardial ischemia marker.6 A clinicalcontext is very important for the interpretation of the value of cTn, the increase of cTn is not always due to Acute Myocardial Infarction(AMI). According to a research, a new cTn examination called ‘high sensitive troponin T’ (hs-cTropT) has a higher sensitivity than theprevious generations for the diagnosis of AMI.7 A 60- year- old female patient entered the ER of Cardiovascular Hospital Harapan Kitasuffering from chest pain since the day before. From the examination it seemed that the patient had a risk factor of dyslipidemia. Thelaboratory results showed normal routine hematology, CKMB , renal function, glucose and electrolytes, however, hs - cTropT and lipidprofile were shown above normal. The differential diagnosis of the symptoms shown was: UA/NSTEMI, with Congestive Heart Failure(CHF) grade II and overweight.